Interplay effects between dose distribution quality and positioning accuracy in total marrow irradiation with volumetric modulated arc therapy. Issue 11 (10th October 2013) - Mancosu, Pietro; Navarria, Piera; Castagna, Luca; Reggiori, Giacomo; Sarina, Barbara; Tomatis, Stefano; Alongi, Filippo; Nicolini, Giorgia; Fogliata, Antonella; Cozzi, Luca; Scorsetti, Marta
Abstract : Purpose: : To evaluate the dosimetric consequences of inaccurate isocenter positioning during treatment of total marrow (lymph‐node) irradiation (TMI‐TMLI) using volumetric modulated arc therapy (VMAT). Methods: : Four patients treated with TMI and TMLI were randomly selected from the internal database. Plans were optimized with VMAT technique. Planning target volume (PTV) included all the body bones; for TMLI, lymph nodes and spleen were considered into the target, too. Dose prescription to PTV was 12 Gy in six fractions, two times per day for TMI, and 2 Gy in single fraction for TMLI. Ten arcs on five isocenters (two arcs for isocenter) were used to cover the upper part of PTV (i.e., from cranium to middle femurs). For each plan, three series of random shifts with values between −3 and +3 mm and three between −5 and +5 mm were applied to the five isocenters simulating involuntary patient motion during treatment. The shifts were applied separately in the three directions: left–right (L‐R), anterior–posterior (A‐P), and cranial–caudal (C‐C). The worst case scenario with simultaneous random shifts in all directions simultaneously was considered too. Doses were recalculated for the 96 shifted plans (24 for each patient). Results: : For all shifts, differences <0.5% were found for mean doses to PTV, body, and organs at risk with volumes >100 cm 3 . Maximum doses increased up to 15% for C‐C shifted plans. PTV covered by the 95% isodose decreased of 2%–8% revealing target underdosage with the highest values in C‐C direction. Conclusions: : The correct isocenter repositioning of TMI‐TMLI patients is fundamental, in particular in C‐C direction, in order to avoid over‐ and underdosages especially in the overlap regions. For this reason, a dedicated immobilization system was developed in the authorsˈ center to best immobilize the patient.